2021
DOI: 10.1128/mbio.00522-21
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Lethal Clostridioides difficile Infection via Intraspecies Competition for Cogerminant

Abstract: Clostridioides difficile, a Gram-positive, spore-forming bacterium, is the primary cause of infectious nosocomial diarrhea. Antibiotics are a major risk factor for C. difficile infection (CDI), as they disrupt the gut microbial community, enabling increased germination of spores and growth of vegetative C. difficile. To date, the only single-species bacterial preparation that has demonstrated efficacy in reducing recurrent CDI in humans is nontoxigenic C. difficile. Using multiple infection models, we determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 54 publications
0
24
1
1
Order By: Relevance
“…This step is potentiated, in vitro, by cholic acid class bile acids and amino acids. In a recent study, Leslie and colleagues demonstrated that consumption of the glycine cogerminant can block the colonization of C. difficile by reducing spore germination [20]. Though we find that C. scindens, C. hiranonis and C. leptum reduce the abundance of glycine, proline and prolylglycine in monoassociated mice (S7 Fig) , we do observe C. difficile colonization but lack of disease (S3 Table ).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…This step is potentiated, in vitro, by cholic acid class bile acids and amino acids. In a recent study, Leslie and colleagues demonstrated that consumption of the glycine cogerminant can block the colonization of C. difficile by reducing spore germination [20]. Though we find that C. scindens, C. hiranonis and C. leptum reduce the abundance of glycine, proline and prolylglycine in monoassociated mice (S7 Fig) , we do observe C. difficile colonization but lack of disease (S3 Table ).…”
Section: Discussioncontrasting
confidence: 41%
“…Bile acid germinants are recognized by the CspC pseudoprotease germinant receptor [8] and the cogerminants (e.g., glycine) are recognized by the CspA pseudoprotease germinant receptor [19]. Recent work has shown that glycine is an important in vivo spore cogerminant and consumption of glycine by one C. difficile strain prevents spore germination (and colonization) by an invading strain [20].…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids metabolized by the gut bacteria can inhibit C. difficile growth and affect toxin production (9,10). Bacteria in the gut also can compete more directly with C. difficile through antibiotic production or nutrient consumption (11)(12)(13). While the relationship between the gut bacteria and C. difficile has been established, the effect the gut bacteria can have on CDI disease severity is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the protection was lost when the colonizing NTCD was removed using vancomycin before the challenge (Borriello and Barclay, 1985). Since then, a variety of animal models have shown that non-toxigenic strains can colonize the GIT and protect against TCD -mediated disease (Borriello and Barclay, 1985;Sambol et al, 2003;Nagaro et al, 2013;de Oliveira Júnior et al, 2016;Oliveira Júnior et al, 2019;Leslie et al, 2021). The first human clinical trial was performed in 1980s where two patients suffering from rCDI were treated with NTCD-M1 strain after vancomycin administration with a 50% clinical success rate (Seal et al, 1987).…”
Section: Introductionmentioning
confidence: 99%